Optical, thermal and dielectric studies of silver-silica nanoparticles synthesized via sol-gel technique - Taifunisyam, T.; Souad A., M.; Mohd Rafie, J.; Wan Jefrey, B.; Chin, K.M.; Chia, C.C.; Tan, J.H. (2014)
Silver-silica nanocomposites (Ag-Si02NCs), with unique properties such as hi~hlY resonant particle plasmons, conductivity and potential applications in optics and varl°t nanoelectronics are very attractive materials for sensing probes in biotechnology. Ag-Si02J>:l ~ with various compositions were synthesized through sol-gel technique. The morphology, opuca and thermal stability of the nanocomposite were investigated and was compared with pure sol-gel t~ determine the effects of the nanoparticles. Transmission electron microscopy (TEM) confirmed tha Si02 was encapsulated Ag with mean size of 30 nm. Uv-vis spectroscopy shows that the surface plasmon resonance (SPR) peak show Ag-Si02 NCs were greatly reduce due to the Si02 particles~ The permittivity and refractive index were decreased as the composition of Ag was increased ad composition of 60% silver. The real permittivity is negative along the visible region. The tren stability of Ag-Si02NCs were increased with the increased amount of silver.